Effects of Process Parameters on Friction Stir Weldability in Dissimilar Joints of AA5052 and Advanced High Strength Steel - Bang, Hee-Seon; Bang, Han-Sur; Kim, Kyoung-Hak (Journal of Welding and Joining, 2021)
The dissimilar joining of aluminum (Al) alloy and steel has become attractive in the automotive sector to achieve lightweight components. However, joining Al to steel using conventional fusion welding processes is difficult be cause of their widely varying thermo-physical properties and the formation of intermetallic compounds (IMCs) at the Al-Fe joint interface. In the present study, the dissimilar joining of a 2.5 mm thick AA5052-H32 and a 1.4 mm thick DP590 steel sheet was performed using friction stir welding (FSW). Moreover, the effects of the process pa rameters on the mechanical properties and microstructure of FS welds was investigated. The tensile test results in dicated that a higher heat input with increasing rotation speed and decreasing travel speed contributed to a higher tensile strength. The maximum tensile strength of the FS welds was 178 MPa, which exhibited a joint efficiency of approximately 79%. As a result of scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS) and X-ray diffraction (XRD) analysis, a thin interfacial layer of less than 1 μm thickness comprising Fe4Al13 IMC was observed at the dissimilar Al-Fe joint interface. KCI Citation Count: 0